ROTATION COMPONENT OF ROBOTIC MANIPULATOR MOTION IN 4-DOF BY THE QUATERNION METHOD - Yasmini, Luh Putu Budi; Isna, Wardah Nur; Risha, Nurfa (Universitas Mataram, 2024)
Most of the study of robots is about the system. Because of that, we analyze the motion of the robot by using rigid body motion concepts. This study aims to analyze the rotation components of a robotic manipulator with four degrees of freedom (4-DoF) by using the quaternion method of manual analysis so that the end effector of the robotic manipulator under study is obtained. The research is theoretical and was conducted through a review and analysis of related literature. Based on the literature review, the robotic manipulator is a robot with a shape resembling an arm. The robotic manipulator consists of bases, links, joins, and an end effector. In terms of physics, the kinematics of robot motion can be studied based on the concept of rigid body motion. The research shows that the quaternion method can be used to determine the end effector of the rotation component of the robotic manipulator, and the steps are shorter than analyses by using screw and twist theory. Based on this case, the end effector of the rotation component depends on the initial state and the total rotation angle of each join.